Gaining Knowledge from Postmortem Analyses to Eliminate Electronic Commerce Project Abandonment - PAN, Gary Shan Chi (Institutional Knowledge at Singapore Management University, 2002)
This paper serves as a stimulus to investigators to examine the role project postmortem analyses plays in learning from abandoned electronic commerce (e-commerce) projects. While prior research has identified the importance of the review process, there has been very little research on project postmortems on abandoned e-commerce projects. The case demonstrates six critical factors to conduct successful project reviews and offers several important managerial guidelines. Finally, when analysing mistakes and their principal causes, there is one important lesson that we should learn. That is, all organisations make mistakes and there is the potential for learning from abandonment experiences.